A formação como aliada no exercício do papel educativo do bibliotecário na escola - Laura Valladares de Oliveira Soares (2014)
This thesis addresses the school librarians education for the exercise of their pedagogical role, although there are in the literature of school library authors who affirm that these professionals do not have sufficient training to fulfill this role. On the other hand, it is known that there are librarians who develop a pedagogical practice in basic education schools. The objective of this research was to understand how the professional librarians education contributed to provide a basis for the exercise of their educational role. As secondary objectives the different aspects of their training that may have influenced the exercise of their educational role and sustained their practice were investigated. It is a qualitative study, whose data were obtained through a semi-structured interview and a form. The sample consisted of 09 librarians working in public and private school libraries of the following states: Rio Grande do Sul (03 informants), São Paulo (informant 01), Rio de Janeiro (01 informant), Belo Horizonte (03 informants), and Espírito Santo (01 informant). The theoretical framework for the research comprised the following themes: a) education and training of librarians; b)the evolution of librarianship curricula in Brazil; c) attitudes and dispositions expected in the librarians profile; d) information literacy training; e) technologies associated with the librarians education of the librarian for research; f) inquiry learning. These topics provided guidance for data collection and analysis. The analysis was performed based on the topics above, exploring in detail the data obtained through interviews. It was concluded that although the participants value and appreciate the educational practices that they develop, in many cases they do not clearly demonstrate the knowledge, attitudes and skills they teach. They see flaws in their academic education and value their practices as a factor of professional development, that allow them to properly perform their educational role.